Listentagram: Inovasi Media Pembelajaran Instagram dalam Keterampilan menyimak pada Siswa Kelas X MA An-Najah I Karduluk Sumenep - Fitri, Novi Amilia; Alatas, Mochammad Arifin; Jamaluddin, Muhammad (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This study is motivated by the low interest and effectiveness of listening learning among tenth-grade students, as well as the development of digital technology. The aim of this research is to describe the implementation of an innovative learning media called ListenTagram (Listening via Instagram) in listening lessons for tenth-grade students at MA An-Najah I Karduluk Sumenep. The subjects of this study were the Indonesian language teacher and 25 tenth-grade students. This research employed a descriptive qualitative approach with data collection techniques including observation and interviews. The data analysis techniques used were data reduction, data display, and conclusion drawing. The results showed that using Instagram as a listening learning medium created a more interactive, enjoyable, and contextual learning atmosphere. Instagram features such as short videos, captions, and comment sections were utilized to train students in understanding meaning, capturing key information, and developing critical responses to audio-visual content. Student participation also increased as they were not only passively listening but also actively interacting with the material and their peers. The conclusion of this study is that ListenTagram is effective as a digital learning innovation that supports the enhancement of listening skills while fostering sustainable learning interest in the digital era.Penelitian ini dilatarbelakangi oleh rendahnya minat dan efektivitas pembelajaran menyimak pada siswa kelas X serta adanya perkembangan teknologi digital. Penelitian ini bertujuan untuk mendeskripsikan penerapan media pembelajaran inovatif bernama ListenTagram (Listening via Instagram) dalam pembelajaran menyimak pada siswa kelas X MA An-Najah I Karduluk Sumenep. Subjek dalam penelitian ini adalah guru mata pelajaran Bahasa Indonesia dan siswa kelas X yang berjumlah 25 orang. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi dan wawancara. Teknik analisis data yang digunakan adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan Instagram sebagai media pembelajaran menyimak menciptakan suasana belajar yang lebih interaktif, menyenangkan, dan kontekstual. Fitur-fitur Instagram seperti video pendek, caption, dan kolom komentar dimanfaatkan untuk melatih siswa memahami makna, menangkap informasi penting, serta mengembangkan respons kritis terhadap konten audio-visual. Partisipasi siswa juga meningkat karena mereka tidak hanya menyimak secara pasif, tetapi juga aktif berinteraksi dengan materi dan rekan sejawat. Simpulan dari penelitian ini adalah bahwa ListenTagram efektif sebagai inovasi pembelajaran digital yang mendukung penguatan keterampilan menyimak sekaligus menumbuhkan minat belajar yang berkelanjutan di era teknologi.